A novel methodology for evaluating wear behavior of rubber composites under combination of sliding and rolling conditions. Issue 9 (16th June 2020) - Wu, Yanping; Dong, Jia; Sun, Congzhi; Li, Jinlong; Chen, Jianmin
Abstract: The wear behavior of tire tread rubber composites has attracted widespread attention of researcher duo to its serious environmental pollution and high frequency of occurrence for a long time. Herein, a new test method is developed, an improved Akron friction testing machine on a laboratory scale was utilized to estimate the wear loss and mechanism of the rubber composites under rolling and sliding coupling condition. The results indicated that the wear loss quickly increases with the increase of the relative sliding velocity. The main wear mechanism, including adhesive, thermofatigue, tear and curl wear, was governed by the thermal deposition of the worn surface. Scanning electron microscope analysis showed thermal decomposition tear region gradually expanded on the worn surface by increasing relative sliding velocity. The heat distribution numerical analysis supported the experimental results, which confirmed that the heat distribution of the worn surface is entirely consistent with the distribution of the thermal decomposition tear region. Abstract :